APPLICATION OF THE NURSING PROCESS IN PEDIATRIC ONCOLOGICAL PALLIATIVE CARE: INTEGRATIVE LITERATURE REVIEW - da Silva Raiol, Leudieny; Freitas Uchoa, Inez; Maria Melo de Oliveira, Denise; dos Santos Chumber, Rayssa; Farah Castanho Ferreira, Milena; Santana do Nascimento, Josilene; de Cassia da Cruz, Gelena; Pinheiro de Moraes Guimarães, Jucinete (Health and Society, 2023)
Objective: Describe the knowledge of the application of the nursing process in pediatric oncology palliative care; Improve quality of life and positively influence the illness process. Methods: This is a qualitative bibliographic study, which will portray the way in which palliative care for children with cancer is approached. Emphasizing the systematization of nurses in the palliative environment. Results: The databases for theoretical support were: ID ONLINE, EEDIC, ISSN and SCIELO. Prioritizing current articles (2016-2020), using only those that were within the time frame and that had an affinity with the theme. Conclusion: It is concluded, then, that palliative care is extremely important, since they begin to be provided from the first care in the hospital until the hospitalization process.